Optical biosensor based on immobilized copper sensitive operon repressor protein for detection of copper ions in water - Ismail, Hassan (2016)
Water pollution, from heavy metals, embodies a latent risk for both terrestrial and aquatic organisms. As such, continuous, simple and sensitive detection tools for toxic metals have been a great challenge of the existing methods used in monitoring of these metals. In this case, biosensors stand worthwhile for constant monitoring of metals in polluted areas. Here a new biosensor based on a tapered Multi-Mode Fiber (MMF) coated with CsoRGZ protein from Geobacillus zalihae (CsoRGz) as a bioreceptor is presented. The optical property of the coated layer changes once it was subjected to copper, resulting in an increase, at the UV-region (240 nm), of the absorption of evanescent waves. This increase of absorption is proportional to the concentration of copper added. The biosensor displayed a continuous response over the range of 5 - 40 μM copper. The limit of detection and limit of quantification were 5 μM and 40 μM copper respectively, with the sensitivity of 0.045 μM-1 based on 20 μm sensor. The biosensor showed a fast response time of 19.8 s at room temperature and pH of 7.0. The biosensor retained its selectivity and did not respond to equivalent additions of cobalt (II) and Nickel (II). This work also revealed, for the first time, the prospect of remote, selective and sensitive monitoring of copper ions in water, from a distance of 50 m, where a continuous response in the range of 5 - 40 μM copper was obtained with no significant difference (p> 0.06) with the non-remote one.